The Effect of Sales and Inventory Forecasting on Net Income: An Exponential Smoothing Model - Raden Rijanto; Nita Konita; Irman Firmansyah (Jurnal Akuntansi dan Sistem Informasi, 2026)
This study examines the effect of sales forecasting and inventory forecasting on net profit in a large company listed on the Indonesia Stock Exchange (IDX) using the exponential smoothing method. The research applies a quantitative approach based on quarterly financial ratio data over nine years, comprising 36 observations selected through purposive sampling. Data analysis includes classical assumption tests, correlation tests, R² evaluation, and partial and simultaneous hypothesis testing using t-statistics and F-statistics at a 0.05 significance level. The findings indicate that sales forecasting has no significant effect on net profit, while inventory forecasting has a positive and significant effect on net profit. Simultaneously, sales forecasting and inventory forecasting positively and significantly affect net profit with moderate predictive power. Accurate forecasting of sales and inventory is essential for reducing uncertainty and supporting effective decision-making related to revenue and profitability.